How Important are Primary Care Physicians and Specialists when Choosing A Medicare Plan (Global Journal of Medical Research, 2016)
A primary care physician can be one of the most important components in the minds of Medicare beneficiaries. Primary care physicians are responsible for providing their patients with preventive care services as well as establishing care for individuals who are ill and require health care services. As a result, the primary care physician coordinates the patient's overall care, including referrals to specialists. The purpose of this paper was to obtain a concrete understating if primary care physicians and specialist play a key role for Medicare recipients when selecting a health care plan. The researcher evaluated the differences between the populations from Miami-Dade County and Broward County participants to determine if there were any similarities. The researcher utilized one research question in order to fulfill the objective of the paper. A total of 16 Medicare beneficiaries from two South Florida counties were interviewed.